Exploring drug repositioning for leishmaniasis treatment: Ivermectin plus polymeric micelles induce immunological response and protection against tegumentary leishmaniasis. (April 2023) - Freitas, Camila S.; Lage, Daniela P.; Machado, Amanda S.; Vale, Danniele L.; Martins, Vívian T.; Cardoso, Jamille M.O.; Oliveira-da-Silva, João A.; Reis, Thiago A.R.; Tavares, Grasiele S.V.; Ramos, Fernanda F.; Ludolf, Fernanda; Pereira, Isabela A.G.; et al.
Graphical abstract: Highlights: Drug repositioning was tested using ivermectin (IVE) against L. amazonensis . It was incorporated into a Poloxamer P407®-containing polymeric micelles system (IVE/M). L. amazonensis -infected mice were treated with free IVE, IVE/M or amphotericin B. Better cellular and humoral response was found in IVE/M-treated animals. The system was not toxic for the animals and reduced the parasite burden. Abstract: Leishmania amazonensis can cause a wide spectrum of the clinical manifestations of leishmaniasis in humans. The development of new therapeutics is a long and expensive task; in this context, drug repositioning could be considered a strategy to identify new biological actions of known products. In the present study, ivermectin (IVE) was tested against distinct Leishmania species able to cause disease in humans. In vitro experiments showed that IVE was effective to reduce the infection degree and parasite load in Leishmania donovani - and L. amazonensis -infected macrophages that were treated with it. In addition, using the culture supernatant of treated macrophages, higher production of IFN-γ and IL-12 and lower levels of IL-4 and IL-10 were found. Then, IVE was used in a pure form or incorporated into Poloxamer 407-based polymeric micelles (IVE/M) for the treatment of L. amazonensis -infected BALB/c mice. Animals (n = 16 per group) were infected and later received saline, empty micelles, amphotericin B (AmpB), IVE, or IVE/M. They were euthanized at one (n = 8 per group) and 30 (n = 8 per group) days after treatment and, in both endpoints, immunological, parasitological, and biochemical evaluations were performed. Results showed that both IVE and IVE/M induced higher levels of IFN-γ, IL-12, GM-CSF, nitrite, and IgG2a antibodies, as well as higher IFN-γ expression evaluated by RT-qPCR in spleen cell cultures. Such animals showed low organic toxicity, as well as significant reductions in the lesion's average diameter and parasite load in their infected tissue, spleen, liver, and draining lymph node. The efficacy was maintained 30 days post-therapy, while control mice developed a polarized Th2-type response and high parasite load. In this context, IVE could be considered as a new candidate to be applied in future studies for the treatment against distinct Leishmania species.